CARACTERIZAÇÃO MORFOLÓGICA DE ACESSOS DE MELOEIRO COLETADOS NO NORDESTE BRASILEIRO - José Torres Filho; Glauber Henrique de Sousa Nunes; José Jaime Cavalcanti Vasconcelos; José Hamilton da Costa Filho; Gabriel Guimarães Costa (Revista Caatinga, 2009)
The objective of the present work was to characterize melon plant accessions collected in the Brazilian Northeast. They were appraised 42 accessions and four you cultivate commercial, in the years of 2006 and 2007, in twoexperiments in randomized blocks with two replications. 24 traits were used, being 1 of the seed, 11 of fruits, 7 inflorescência, 4 of the leaf and 2 of the plant. The accesses belonged to the botanical group Cantalupensis, Momordica, Conomon and not defined group. Great variation was observed among the accessions for all the traits, especially in the fruit descritores. Variation was verified among and within of the studied botanical groups, mainly in the group Cantalupensis. In a general way, the accesses were fruitful, productive, with long fruits of intermediate size the big ones, with low pulp firmness and lower content of soluble solids. The characterization of the accessions with relationship to the fruit traits can aid the improvement programs. Some accessions can be used to increased the fruitful and the productivity of the melon through crossings with elite cultivars.